Using the Sibelius program in music education - Dadaboyev Hasanboy Maratovich (Research Parks Publishing LLC, 2021)
The article highlights that Sibelius program - manual typing of notes, playing them on the MIDI keyboard, or simply opening the desired MIDI file and processing it after a while to create the score scores that will turn into a completely finished score. is a program with a wide range of capabilities. They will also know that you can print the scores of works at the level of publishing quality and save them as ready-made pictures or Web pages. You can also listen to the music you create at any time, save it in audio format (MIDI or WAV), and then (using tools specifically designed for this program) to record a music CD or audio video from WAV files.